Factors Impacting College Student Satisfaction, Perceived Usefulness, and Continuance Intention with E-learning in Dezhou, China - Yang, Hongjie (Scholar: Human Sciences, 2024)
Purpose: The study aims to identify significant factors impacting junior college students’ continuance intentions to use e-learning at a public university in Dezhou, China. The research model is constructed with key constructs: perceived ease of use, perceived usefulness, system quality, information quality, self-efficacy, satisfaction, and continuation intention. Research design, data, and methodology: The researcher applied a quantitative method by distributing an online questionnaire to 495 respondents who are junior college students in four majors at public institutions in Dezhou, China. The sampling techniques were applied in this study, including purposive, quota, and convenience sampling. Confirmatory factor analysis (CFA) and structural equation modeling (SEM) were used to determine the significant relationships and hypotheses testing results. Results: The findings demonstrate that satisfaction strongly influenced continuance intention. Information quality, perceived ease of use, system quality, and perceived usefulness significantly impact satisfaction. Perceived ease of use and self-efficacy has a significant impact on perceived usefulness. Conclusions: University administrators and teaching staff should pay attention to developing significant factors that encourage students to continue using e-learning more effectively. Educators should consider reforming future learning according to the findings of this research, which will help students acknowledge and recognize the effectiveness of online education.